1986
DOI: 10.1002/anie.198607901
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis of Anthracyclinone [New Synthetic Methods (60)]

Abstract: The remarkable antitumor properties of anthracycline antibiotics have motivated synthetic chemists, and a large number of groups have been active recently in this field. Initially, there was very little hope for this class of substances due to their extreme toxicity. However, the dividing line between toxicity and desired pharmacological effect has broadened to such an extent, partly through microbiological methods (new strains, mutants) and partly through semisynthetic modifications, that today anthracyclines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(10 citation statements)
references
References 177 publications
0
10
0
Order By: Relevance
“…8.12; 75), the first member of a very interesting bisindolobenzoquinone class of compounds, in the year 1975, from Chaetomium sp., as antifungal antibiotic compound. Since then several benzoquinones, such as asterriquinones [81][82][83][84] (76)(77)(78)(79)(80)(81)(82)(83)(84), isocochliodinol (85), semicochliodinols (86, 87) [89], and terphenylquinones (88)(89)(90)(91)(92), were isolated [90][91][92]. Although asterriquinones were well recognized for their antibiotic and antitumour activity [87], it took around 25 years to realize their kinase inhibitory potential [85,86,88].…”
Section: Benzoquinones (Table 83)mentioning
confidence: 99%
“…8.12; 75), the first member of a very interesting bisindolobenzoquinone class of compounds, in the year 1975, from Chaetomium sp., as antifungal antibiotic compound. Since then several benzoquinones, such as asterriquinones [81][82][83][84] (76)(77)(78)(79)(80)(81)(82)(83)(84), isocochliodinol (85), semicochliodinols (86, 87) [89], and terphenylquinones (88)(89)(90)(91)(92), were isolated [90][91][92]. Although asterriquinones were well recognized for their antibiotic and antitumour activity [87], it took around 25 years to realize their kinase inhibitory potential [85,86,88].…”
Section: Benzoquinones (Table 83)mentioning
confidence: 99%
“…: [5] 164-165°C). 1 Oxidative Cleavage of (R)-5 and Transformation to (R)-Fridamycin E Methyl Ester: NaIO 4 (206 mg, 0.97 mmol, 8 equiv.) was added to a solution of (R)-5 (37 mg, 0.12 mmol) in acetone/water (9:1, 2 mL) and the mixture was cooled to 0°C.…”
Section: Coupling Of Epoxide (S)-4a To Stannanementioning
confidence: 99%
“…The clinical utility of anthracyclines and their analogs in chemotherapy has initiated many efforts directed towards their synthesis. [1,2] Typically, anthracyclines consist of an anthraquinone nucleus bearing one or more sugar moieties attached through O-glycosidic bonds. However, an intriguing subclass of structurally related compounds exists in which the carbohydrate is linked by a C-glycosidic bond, prominent representatives of which are the vineomycin [3] and fridamycin families.…”
Section: Introductionmentioning
confidence: 99%
“…A brief literature survey revealed that the routes for the synthesis of anthraquinones are primarily based upon five categories, such as Friedel–Crafts reactions, Hauser annulations, Diels–Alder reactions, transition metal-mediated reactions and biomimetic aldol condensations [ 17 23 ], and reports on the synthesis of brominated anthraquinones are scare [ 12 15 ]. Having inspired by the convergence and the regiochemical integrity of the Hauser annulation [ 24 30 ], we explored it for the construction of the bromoanthraquinone scaffolds of proisocrinins 6 – 11 .…”
Section: Introductionmentioning
confidence: 99%